2019
DOI: 10.1088/1742-6596/1232/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristic of probiotic ice cream substituted by encapsulated lactic acid bacteria (LAB) with variety of aging time

Abstract: Probiotic ice cream is one of methods in improving benefit and functional value of common ice cream. This research studies about the effect of probiotic added in form of capsules and maturation (aging) time on the physical quality and sensory acceptability. The article presents data of overrun, melting time, viscosity, and panelists’ preferences in terms of probiotic ice cream characteristics. The data is calculated statistically by using ANOVA. The results show that aging time determines most of evaluated phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In another study investigated by Sagdic, Ozturk, Cankurt, and Tornuk (), who concluded that the addition dietary fiber and culture cause an increase in acidity and decrease in pH. The supplementation of encapsulated probiotic bacteria in ice cream positively improve the physical quality parameters of ice cream during storage and using of different aging time affect the physical quality of probiotic ice cream (Muhardina, Sari, Aisyah, & Haryani, ).…”
Section: Resultsmentioning
confidence: 98%
“…In another study investigated by Sagdic, Ozturk, Cankurt, and Tornuk (), who concluded that the addition dietary fiber and culture cause an increase in acidity and decrease in pH. The supplementation of encapsulated probiotic bacteria in ice cream positively improve the physical quality parameters of ice cream during storage and using of different aging time affect the physical quality of probiotic ice cream (Muhardina, Sari, Aisyah, & Haryani, ).…”
Section: Resultsmentioning
confidence: 98%
“…This suggests that adding CCE to ice cream enhances its overrun and that this impact is magnified when probiotic bacteria are present. Muhardina et al (2019) reported a similar finding in probiotic ice cream substituted by encapsulated LAB. In another study, the symbiotic ice cream made from fermented milk had the highest overrun (Golestani & Pourahmad, 2016).…”
Section: Resultsmentioning
confidence: 63%
“…This suggests that adding CCE to ice cream enhances its overrun and that this impact is magni ed when probiotic bacteria are present. Muhardina et al (2019) reported a similar nding in probiotic ice cream substituted by encapsulated LAB. The bacterial cells and/or small particles of CCE along the fat globules may be causing the increase in overrun by trapping air in the ice cream mixture and increasing the volume.…”
Section: Overrunmentioning
confidence: 67%